Antioxidant Potential of Organic Fraction of Turi Leaf Extract (Sesbania grandiflora L.) Using DPPH Reagent - Wa Ode Sitti Musnina; Randa Wulaisfan; Jumriana Akhyar; Yonelian Yuyun (Halu Oleo University, 2022)
Background: White turi leaf (Sesbania grandiflora) is a plant from the Leguminosae family that isused as traditional medicine. Purpose(s): To determine the antioxidant potential of white turi leafextract (Sesbania grandiflora L) using DPPH reagent. Methods: White turi leaves (S. grandiflora)were extracted using maceration technique with ethanol the solvent. The ethanol extract wasfractionated using a liquid-liquid extraction using n-hexane, ethyl acetate, and ethanol. In addition,phytochemical screening was also carried out on secundary metabolite compounds contained in theethanol extract, it’s organic fractions. Results: Ethanol extract obtained as much as 160 g (16%).Fractionation of 10 grams of ethanol extract obtained n-hexane fraction 2.9 g (29%); ethyl acetatefraction 0.8 g (8%); and ethanol fraction 6.1 g (61%). Phytochemical screening showed that theethanol extract and ethyl acetate fraction contained flavonoids, saponins, and tannins; the ethanolfraction contains terpenoids, flavonoids, saponins, and tannins; while the n-hexane fraction containstannin compounds. The antioxidant activity of the ethanol extract, ethyl acetate fraction, and ethanolfraction were tested using the DPPH radical scavenging method. The antioxidant activity assayshowed that the SC50 values of the ethanol extract, ethyl acetate fraction, and ethanol fraction were234.7; 66,244, and 106.755 ppm, vitamin C as a positif control with SC50 3,006 ppm. Conclusion:white turi leaf extract (S. grandiflora) has antioxidant activity less than 22-78 times than controlpositif, so it is not potential as an antioxidant.